This distracted and anarchical people new answers for old questions about the Civil War-era North - Slap, Andrew L.; Smith, Michael Thomas 1970- (North's Civil War., 2013)
The essays in this book range widely throughout the history of the Civil War North, using new methods and sources to re-examine old theories and discover new aspects of America's greatest conflict. Many of these issues are just as important today as they were a century and a half ago.